3D brown adipogenesis to create "Brown-Fat-in-Microstrands". (January 2016) - Unser, Andrea M.; Mooney, Bridget; Corr, David T.; Tseng, Yu-Hua; Xie, Yubing
Abstract: The ability of brown adipocytes (fat cells) to dissipate energy as heat shows great promise for the treatment of obesity and other metabolic disorders. Employing pluripotent stem cells, with an emphasis on directed differentiation, may overcome many issues currently associated with primary fat cell cultures. In addition, three-dimensional (3D) cell culture systems are needed to better understand the role of brown adipocytes in energy balance and treating obesity. To address this need, we created 3D "Brown-Fat-in-Microstrands" by microfluidic synthesis of alginate hydrogel microstrands that encapsulated cells and directly induced cell differentiation into brown adipocytes, using mouse embryonic stem cells (ESCs) as a model of pluripotent stem cells, and brown preadipocytes as a positive control. Brown adipocyte differentiation within microstrands was confirmed by immunocytochemistry and qPCR analysis of the expression of the brown adipocyte-defining marker uncoupling protein 1 (UCP1), as well as other general adipocyte markers. Cells within microstrands were responsive to a β-adrenergic agonist with an increase in gene expression of thermogenic UCP1, indicating that these "Brown-Fat-in-Microstrands" are functional. The ability to create "Brown-Fat-in-Microstrands" from pluripotent stem cells opens up a new arena to understanding brown adipogenesis and its implications in obesity and metabolic disorders.